Cooperative control of battery energy storage systems in microgrids - Hosseinimehr, Tahoura; Ghosh, Arindam; Shahnia, Farhad (Elsevier, 2017)
Â© 2016 Elsevier Ltd This paper proposes a cooperative control of battery energy storage (BES) units within a microgrid (MG) which includes two control subsystems for charge and discharge operation mode of the BES. In addition, the proposed cooperative control strategy provides accurate reactive power sharing among the BES units. During discharge operation, the proposed strategy utilizes a SoC-based droop control in order to avoid promptly depleting of the BES units, by dedicating the highest priority to their SoC level and respecting their power rating. This is achieved without any disturbance in the power balance of the MG. In addition, during charge operation of the BES units, the proposed control method uses a proportional-integral (PI) controller to limit the BES absorbing power and match it with the available surplus power from the renewable energy sources (RESs). This in turn avoids any power imbalance within the system. Finally, to utilize the extra capacity of the BES converters and also to avoid overloading of RESs, a new adaptive virtual impedance (AVI) strategy is proposed here which provides accurate reactive power sharing by imposing a virtual impedance in series with the coupling impedance of each BES and RES unit. The system performance is validated through extensive simulations carried out in PSCAD/EMTDC software.